Ordinance No. 13: An Act to Prohibit the Carrying of Concealed Weapons, OKEENE EAGLE, Mar. 10, 1902, at 1 (Okeene, Oklahoma). - (:unkn) unknown (General Publisher, 1902)
It shall be unlawful for any person to carry upon his person any concealed pistol, revolver, dirk, bowie knife, billy, sling shot, metal knuckles, or other dangerous or deadly weapons of any kind, excepting only officers of the law in the discharge of their duties
--
Keywords: CARRY - CONCEALED